Upaya Pemerintah Indonesia Dalam Meningkatkan Wisatawan Mancanegara Asal Singapura Melalui Program Wonderful Indonesia Tahun 2011-2014 - Bazher, Salamah Salem (Global and Policy Journal of International Relations, 2016)
ABSTRACTThis study aims to explain the Indonesian government's efforts to increase foreign tourists from Singapore through the Wonderful Indonesia program in 2011-2014. The background of this study is the fluctuations of the number of foreign tourists to Indonesia from year 2004 to 2010, the declining occurs due to the international issues stating that Indonesia is an unsafe country. Therefore, Indonesia made various efforts to attract foreign tourists to visit Indonesia. Wonderful Indonesia is a program created by the Indonesian government as an effort to bring back the high number of foreign tourists. Wonderful Indonesia officially implemented from the beginning of January 2011. Singapore became the main promotion target of the Wonderful Indonesia program because Singaporean tourist is biggest contributor for the total number of tourists visiting Indonesia that has been showing a declining trend. Those problems are being analyzed under a dekskriptif methode by employing the cultural diplomacy and tourism promotion framework. Based on the theoretical approach, it can be argued that the government's efforts is based on a form of cultural diplomacy. This form of cultural diplomacy by Indonesia to Singapore works though the promotion of tourism and the forms of tourism promotion, specifically through sales promotion, internet marketing and advertising.Keywords: Wonderful Indonesia, cultural diplomacy, and tourism promotionDOI : https://doi.org/10.33005/jgp.v4i01.1929